Export licensing in the WTO context - Carlo Gamberale; Irina Tarasenko (World Trade Organization (WTO), 2023)
This paper addresses the issue of export licensing procedures in the WTO context. It aims to contribute to the understanding of the existing rules applicable to export licensing in the WTO, and what the development of specific disciplines would mean to international trade. The paper looks at the definition of export licensing, the past discussions on developing specific rules on export licensing in the GATT and in the WTO, the existing WTO rules applicable to export and import licensing of goods and services, and the surge in export restricting measures and export licensing implemented by several Members in the context of COVID-19 pandemic and the conflict in Ukraine.
Keywords: F17; F13; 330; trade policy; export licensing; export restrictions